Eicosanoids and Their Drugs in Cardiovascular Diseases: Focus on Atherosclerosis and Stroke. Issue 2 (20th March 2012) - Capra, Valérie; Bäck, Magnus; Barbieri, Silvia S.; Camera, Marina; Tremoli, Elena; Rovati, G. Enrico
Abstract Eicosanoids are biologically active lipids in both physiologic and pathophysiologic situations. These mediators rapidly generate at sites of inflammation and act through specific receptors that following the generation of a signal transduction cascade, lead to coordinated cellular responses to specific stimuli. Prostanoids, that is, prostaglandins and thromboxane A2, are active products of the cyclooxygenase pathway, while leukotrienes and lipoxins derive from the lipoxygenase pathway. In addition, a complex family of prostaglandin isomers called isoprostanes is derived as free‐radical products of oxidative metabolism. While there is a wide consensus on the importance of the balance between proaggregating (thromboxane A2) and antiaggregating (prostacyclin) cyclooxygenase products in cardiovascular homeostasis, an increasing body of evidence suggests a key role also for other eicosanoids generated by lipoxygenases, epoxygenases, and nonenzymatic pathways in cardiovascular diseases. This intricate network of lipid mediators is unique considering that from a single precursor, arachidonic acid, may derive an array of bioproducts that interact within each other synergizing or, more often, behaving as functional antagonists.